O ofício de interpretar: objeto enquanto aparência e realidade à luz da filosofia de Peirce - Di Sarno, Ivani Cunha (2000)
In this text, we have sought to demonstrate how we can interpret the object as an appearance and as a reality, according to the philosophy of Peirce, as explained based in triadic logic of symbol interpretation. The construction of this logic is developed in phenomenology, through the categories of Firstness, Secondness and Thirdness, the last one playing the main role in the works of the author. It acts as a mediator for an action of trivalent nature, refuting all diadic concepts, or diadic representations of sign-object, or object-sign, thus "breaking" with the pretention of interpreting in a single absolute way the traditional dichotomy. The first part of this dissertation deals with the development of structure in the philosophical thinking of Peirce, evincing the importance of pragmatism as a method of scientific research. The second part discusses the problem of interpretation, in wich the object as an appearance is studied in phenomenology, and the object as a reality within the Metaphisics of the author. The object is decomposed by the analysis of these sciences and later reconstituted in Semiotics, remade in its totality, in the sign-object-interpreter triad. Therefore, to ensure interpretation as a triadic process, based on this triad, it is necessary for Semiotics to play the main role in the elaboration of this process